A comparison of the perceived added value of PSS applications in group settings. (March 2016) - Pelzer, Peter; Geertman, Stan; van der Heijden, Rob
ABSTRACT: Research on planning support systems (PSS) is increasingly paying attention to the added value that PSS applications have for planning practice. Whereas early studies tended to have a rather conceptual focus, recent studies have paid more attention to empirics. Although this is a step forward, there is still a notable gap in the literature: a dearth of empirical evaluations of PSS applications from a comparative perspective. This paper addresses this gap, based on an earlier published conceptual framework that identifies the potential added values of PSS applications. The paper also tentatively explores the effect of three explanatory factors: support capabilities of the PSS, usability, and the context. In doing so, it reports on research of four PSS applications in The Netherlands. The research method consisted of questionnaires completed directly after the session, open interviews and conversations with stakeholders, and observations. With regard to added value as perceived by the participants, the findings indicate that learning, both about the object and about others, was a key perceived added value in all four cases, despite differences in context, support capabilities and usability scores. Moreover, although usability perceptions of the PSS applications varied, overall they were relatively positive. Context appears to have a substantial effect on the perceived added value of the PSS application, making it hard to distil the exact effect of the support capabilities and usability perceptions. The effect of context is one of the topics that could be picked up in further studies into the added value of PSS. One way to accomplish this in future research is by comparing a larger number of different PSS applications in different contexts, resulting in a higher n in order to enable correlational analyses and cross-national comparisons to better grasp the influence of the institutional context. Highlights: Comparative studies into the perceived added value of applying Planing Support Systems in group settings are lacking. This paper aims to fill this gap through an empirical study conducted in four PSS applications in the Netherlands. Learning, both about the object and others, is the most frequently perceived as an added value of PSS applications. The low n precludes advanced statistical analysis, future research could address this.